AN ANALYSIS COMPARING ENGLISH AND UZBEK APHORISMS ON THE CONCEPT OF “POVERTY” (TAMADDUN NURI JURNALI, 2025)
This article is dedicated to the specific structural aspects of Uzbek aphorisms about poverty. The importance, historical value, cultural aspects of aphorisms, and stylistic means of description were analyzed. At the same time, the opinions expressed by famous linguists and their work are shown.